AMS dating and ancient DNA analysis of bone relics associated with St John the Baptist from Sveti Ivan (Sozopol, Bulgaria) - Rossina Kostova; Kazimir Popkonstantinov; Hannes Schroeder; Eske Willerslev; Aleksander Sultanov; Georges Kazan; Thomas Higham (Elsevier, 2022)
Excavations in 2010 on the Black Sea island of Sveti Ivan (Bulgaria) revealed the remains of a miniature marble sarcophagus containing human and animal remains, along with an inscribed tufa ossuary, beneath a 4th to 5th-century church floor. The inscriptions on the ossuary suggest links to John the Baptist since they refer to him by name and contain a reference to his nativity date of June 24. The ancient Greek also mentions him in the genitive case, i.e. ‘of Saint John’. Here, we review the historical evidence pertaining to the relics and conclude that they most likely reached Sveti Ivan via Constantinople during the 4-5th century AD. To shed more light on the relics, we sampled three of the remains for radiocarbon dating and ancient DNA analysis. Radiocarbon dating of one of the bones (a phalange) yielded a first century AD date (5-75 cal AD, 68.2% probability). Ancient DNA analysis of the finger bone as well as a rib fragment and a tooth, using shotgun sequencing yielded very little human DNA, ranging between 0-0.9% of sequenced reads. However, the DNA did not show any of the post-mortem damage patterns that are typical for ancient DNA. We conclude that the sequences we obtained are most likely the result of modern contamination.